Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1200/jco.2020.38.15_suppl.3079
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of sintilimab plus different dose of IBI305 (anti-VEGF monoclonal antibody) in patients with advanced hepatocellular carcinoma: A phase Ib study.

Abstract: 3079 Background: The study aimed to evaluate the safety and efficacy of sintilimab, a PD-1 blockade, plus IBI305, a biosimilar candidate of bevacizumab, in patients (pts) with advanced hepatocellular carcinoma (HCC). Methods: Adults with histocytologically confirmed advanced or metastatic HCC were enrolled in this two-part study. Part 1 was dose escalation trial, with initial dose of sintilimab 200 mg plus IBI305 7.5 mg/kg, q3w (low-dose group). If tolerable, IBI305 was escalated to 15 mg/kg (high-dose group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…This study achieved a similar efficacy compared to that of IMbrave150. Moreover, the overall ORRs of other first-line combination therapies in trials that are still ongoing have ranged from 29 to 54.2%, and those studies have been based primarily on western HCC patients ( 15 17 , 19 , 20 , 26 ). In the current study, more than 60% of the patients were HBV-positive, yet achieved an ORR of 31%, similar to the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study achieved a similar efficacy compared to that of IMbrave150. Moreover, the overall ORRs of other first-line combination therapies in trials that are still ongoing have ranged from 29 to 54.2%, and those studies have been based primarily on western HCC patients ( 15 17 , 19 , 20 , 26 ). In the current study, more than 60% of the patients were HBV-positive, yet achieved an ORR of 31%, similar to the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis of IMbrave150 highlighted the efficacy and safety of treatment with atezolizumab plus bevacizumab in the Chinese HCC population (19), and more trials of PD-1/L1 inhibitors combined with anti-angiogenic drugs for HCC in China are underway, but the sample size of which is small (20)(21)(22). Current research of first-line immunotherapy for HCC patients in China is relatively limited; there remains an urgent need for additional effective and safe treatments of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…The TKIs used in this study were lenvatinib (8 mg/day regardless of patient body weight) or apatinib [22] (250 mg/day). Anti-PD-1 antibodies were intravenously administered as follows: nivolumab 3 mg/kg, or camrelizumab [23] 200 mg, every 2 weeks or pembrolizumab 200 mg, or sintilimab [24] 200 mg, every 3 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…It has been available for patients with advanced cancer in China since 2019. Preliminary results of a phase Ib study showed treatment with sintilimab plus VEGF mAb IB305 resulted in an ORR of 33.3% and a 6-month PFS of 60.5% in patients with advanced HCC (16). A phase 3 ORIENT-32 study evaluating the efficacy and safety of sintilimab plus IB305 as a first-line treatment for advanced HCC is underway (NCT03794440).…”
Section: Introductionmentioning
confidence: 99%